2015
DOI: 10.1021/acs.jpcc.5b07525
|View full text |Cite
|
Sign up to set email alerts
|

Solvation and Reaction of Ammonia in Molecularly Thin Water Films

Abstract: Determining the interaction and solvation structure of molecules with solvents near a surface is of fundamental importance for understanding electro-and photochemical processes. Here we used scanning tunneling microscopy (STM) to investigate the adsorption and solvation structure of ammonia on water monolayers on Pt(111). We found that at low coverage NH 3 binds preferentially to H 2 O molecules that are slightly elevated from the surface and weakly bound to the metal. Density functional theory (DFT) calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…This finding is consistent with the LES results, which indicatet hat the main protonated water clusters on the Pt (111) ions, we determinedt he optimized structure for protonh ydration in aw ater monolayer.I nt he previous study,i tw as proposed that aw ater layer on ah ydrogen-adsorbed Pt(111)s urface prefers ( p 3 p 3)R308 (R3) structures. [15] Therefore, we optimized the proton-containing water monolayer structure generated by adding an additional hydrogen atom to the water molecule orienting parallelt ot he Pt surface in the R3 water monolayer.A lthougho ther structures[ ( p 37 p 37)ÀR25.38 or ( p 39 p 39)ÀR16.18]a re also possible for water monolayerso np latinum, [16] proton hydrationi nt hese structures seems to resemble that in the R3 monolayer.T hus, the structure estimated from the R3 monolayer seemsa dequate foruse as an initial configuration to be optimized. By using DFT optimization calculations, as described in the Methods Section, we obtaineda no ptimized proton hydration structurei nawater monolayer,a sp resented in Figure 3(a).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with the LES results, which indicatet hat the main protonated water clusters on the Pt (111) ions, we determinedt he optimized structure for protonh ydration in aw ater monolayer.I nt he previous study,i tw as proposed that aw ater layer on ah ydrogen-adsorbed Pt(111)s urface prefers ( p 3 p 3)R308 (R3) structures. [15] Therefore, we optimized the proton-containing water monolayer structure generated by adding an additional hydrogen atom to the water molecule orienting parallelt ot he Pt surface in the R3 water monolayer.A lthougho ther structures[ ( p 37 p 37)ÀR25.38 or ( p 39 p 39)ÀR16.18]a re also possible for water monolayerso np latinum, [16] proton hydrationi nt hese structures seems to resemble that in the R3 monolayer.T hus, the structure estimated from the R3 monolayer seemsa dequate foruse as an initial configuration to be optimized. By using DFT optimization calculations, as described in the Methods Section, we obtaineda no ptimized proton hydration structurei nawater monolayer,a sp resented in Figure 3(a).…”
Section: Resultsmentioning
confidence: 99%
“…The work reported herein was aimed at understanding recent studies of molecular adsorption on among the best understood of water monolayers, the p 37 ⇥ p 37-R25.3 and p 39 ⇥ p 39-R16.1 periodic water molecule arrangements on Pt(111). 2 Experiments by Kimmel et al, 3 and by Lechner et al, 4 have shown that CO, 3 N 2 , 3 and NH 3 4 molecules stick to these water layers at temperatures as low as 20 K, implying that if there is a barrier to adsorption, it is not large.…”
mentioning
confidence: 98%
“…But, STM images are available for NH 3 , and they show it adsorbing at specific sites on the water-covered surface. 4 This means NH 3 sticks not as a physisorbed molecule, delocalized over the water layer, but through hydrogen bond formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The thickness of surface water layer increases with increase in RH. 48 The presence of water layer on the sensor surface can enhance the adsorption of ammonia gas molecule, as reported by Lechner et al 49 The following acid-base reaction of NH 3 with H 2 O forms aqueous ammonia with protonated NH 4 + :…”
Section: Humidity Analysismentioning
confidence: 86%